Evaluating the impact of risk management and cybersecurity on decision-making in the Peruvian National Informatics System - Estrada, Frank Agustín Olivos; Flores-Sotelo, Willian Sebastian; Barrera-Avalos, Carmen Rosa; Martínez-Aberga, Williams Arturo; Sulca-Guillen, Richard; Chávez-Díaz, Jorge Miguel (Institute of Advanced Engineering and Science, 2025)
This research addresses the influence of risk management (RM) and cybersecurity (CIB) on decision making (DM) of the Peruvian State's National Informatics System (SNIEP) in the year 2024, in line with sustainable development goal 9. Using a quantitative, non-experimental, cross-sectional design approach, a sample of 487 CIB analysts was analyzed to explore the relationship between these critical variables. The findings show uneven implementation of RM and CIB practices, which significantly impact the DM and quality of information (Sig 0.000), processes (Sig 0.001), and the effectiveness of system decisions (Sig 0.060). In addition, key areas were identified to strengthen the integration of RM and CIB strategies in the state's digital environment, highlighting their importance to ensure informed and resilient decisions in the face of growing cyber threats. The study provides empirical evidence on their impact on the quality, effectiveness and security of DM in government digital environments. The research contributes both to the development of a theoretical framework that articulates concepts of RM, CIB, and DM in the public sector, and to the formulation of strategies and policies that promote a secure and efficient digital infrastructure, aimed at improving public services and citizen trust in the contemporary digital environment.